Cardiac output improvement by pecavaptan: a novel dual‐acting vasopressin V1a/V2 receptor antagonist in experimental heart failure. (9th October 2020) - Mondritzki, Thomas; Mai, Thuy Anh; Vogel, Julia; Pook, Elisabeth; Wasnaire, Pierre; Schmeck, Carsten; Hüser, Jörg; Dinh, Wilfried; Truebel, Hubert; Kolkhof, Peter
Abstract : Aims: Arginine vasopressin (AVP) mediates deleterious effects via vascular V1a and renal V2 receptors in heart failure (HF). Despite positive short‐term decongestive effects in phase II HF studies, selective V2 receptor antagonism has shown no long‐term mortality benefit, potentially related to unopposed V1a receptor activation. We compared the novel dual V1a/V2 receptor antagonist pecavaptan with the selective V2 receptor antagonist tolvaptan in pre‐clinical HF models. Methods and results: In vitro IC50 determination in recombinant cell lines revealed similar receptor selectivity profiles (V2:V1a) of tolvaptan and pecavaptan for human and dog AVP receptors, respectively. Two canine models were used to compare haemodynamic and aquaretic effects: (i) anaesthetised dogs with tachypacing‐induced HF, and (ii) conscious telemetric dogs with a non‐invasive cardiac output (CO) monitor. Tolvaptan and pecavaptan exhibited no differences in urinary output. In HF dogs, pecavaptan counteracted the AVP‐induced increase in afterload and decrease in CO (pecavaptan: 1.83 ± 0.31 L/min; vs. tolvaptan: 1.46 ± 0.07 L/min, P  < 0.05). In conscious telemetric animals, pecavaptan led to a significant increase in CO (+0.26 ± 0.17 L/min, P  = 0.0086 vs. placebo), in cardiac index (+0.58 ± 0.39 L/min/m 2, P  = 0.009 vs. placebo) and a significant decrease in total peripheral resistance (−5348.6 ± 3601.3 dyn × s/cm 5, P  < 0.0001 vs. placebo), whereas tolvaptan was without any significant effect. Conclusions: Simultaneous blockade of vascular V1a and renal V2 receptors efficiently induces aquaresis and counteracts AVP‐mediated haemodynamic aggravation in HF models. Dual V1a/V2 antagonism may lead to improved outcomes in HF. Abstract : Graphical abstract demonstrating the beneficial effect of dual vasopressin antagonism. AVP, arginine vasopressin; CO, cardiac output; TPR, total peripheral resistance; UV, urine volume.